Warrumbungle Volcano: facies architecture and evolution of a complex shield volcano. Issue 2 (17th February 2021) - Bull, K. F.; Troedson, A. L.; Bodorkos, S.; Blevin, P. L.; Bruce, M. C.; Waltenberg, K.
Abstract: We present a new geological map of Warrumbungle Volcano created from volcanic facies field mapping, new geophysical, geochemical and geochronological data as well as data from previous studies. Field mapping and petrography defined 19 volcanic and two mixed volcanic--sedimentary facies. Facies identification and distribution in conjunction with geochemical analyses indicate an early shield-forming phase of predominantly mafic and intermediate lavas and pyroclastic deposits, and minor felsic lavas deposited on an irregularly eroded basement of Surat and Gunnedah basin rocks. The shield was subsequently intruded by felsic intermediate to felsic magmas that formed dykes and other intrusions, including possible cryptodomes, and also erupted as lava domes and block-and-ash-flow deposits. A radial dyke swarm cross-cuts most units, although it is concentrated within basement sandstone surrounding the central area of the volcano, suggesting late inflation accompanied by dyke emplacement. Geochemistry indicates differentiation of a single although repeatedly recharged alkaline magmatic suite. Fractionation of olivine, Ti-magnetite and clinopyroxene occurred in mafic magmas, and after reaching 62 wt% SiO2, crystallisation of apatite and alkali feldspar took place. A new U–Pb zircon SHRIMP magmatic crystallisation age of 16.25 ± 0.12 Ma on a felsic block-and-ash flow deposit is in agreement with the recalculated 40 Ar/ 39 Ar isochron dates of previous workers. Based on our mapping and the use of volcanic facies to define mappable units, we recommend that the previous Warrumbungle Volcanics be elevated from formation to group status and renamed the Warrumbungle Volcanic Complex. KEY POINTS: New geological map of Warrumbungle Volcano based on volcanic facies mapping. The volcanic facies and their distribution suggest a complex alkaline shield volcano erupted along regional-scale basement lineaments over an intracontinental 'hot-spot' or heat plume, and intruded by lava domes, cryptodomes, dykes and a radial dyke swarm. New and previous geochemical data suggest differentiation of a single, although repeatedly recharged, alkaline magmatic suite. A new U–Pb zircon SHRIMP date of 16.25 ± 0.12 Ma is in agreement with the recalculated 40 Ar/ 39 Ar isochron dates of previous workers.